Virulence-Associated Secretion in Mycobacterium abscessus - Bar-Oz, Michal; Meir, Michal; Barkan, Daniel (Frontiers in Immunology, 2022)
Non-tuberculous mycobacteria (NTM) are a heterogeneous group of originally environmental organi3sms, increasingly recognized as pathogens with rising prevalence worldwide. Knowledge of NTM’s mechanisms of virulence is lacking, as molecular research of these bacteria is challenging, sometimes more than that of M. tuberculosis (Mtb), and far less resources are allocated to their investigation. While some of the virulence mechanisms are common to several mycobacteria including Mtb, others NTM species-specific. Among NTMs, Mycobacterium abscessus (Mabs) causes some of the most severe and difficult to treat infections, especially chronic pulmonary infections. Mabs survives and proliferates intracellularly by circumventing host defenses, using multiple mechanisms, many of which remain poorly characterized. Some of these immune-evasion mechanisms are also found in Mtb, including phagosome pore formation, inhibition of phagosome maturation, cytokine response interference and apoptosis delay. While much is known of the role of Mtb-secreted effector molecules in mediating the manipulation of the host response, far less is known of the secreted effector molecules in Mabs. In this review, we briefly summarize the knowledge of secreted effectors in Mtb (such as ESX secretion, SecA2, TAT and others), and draw the parallel pathways in Mabs. We also describe pathways that are unique to Mabs, differentiating it from Mtb. This review will assist researchers interested in virulence-associated secretion in Mabs by providing the knowledge base and framework for their studies.